Respostas

2014-08-31T00:00:17-03:00
3a(a-b)-2a(a+b)
3a²-3ab-2a²-2ab
a²-5ab

2x(x-3)+x(x-5) 
2x²-6x+x²-5x
3x²-11x

(x-3).(x-5)+3x(x+4) 
x²-5x-3x+15+3x²+12x
4x²-8x+12x
4x²+4x

(a+b).(a-b)+(a-2b).(a+5b)
a²-ab+ab-b²+a²+5ab-2ab-10b²
2a²+3ab-11b²
  • Usuário do Brainly
2014-08-31T04:49:28-03:00
Olá, Laura !

Utilize distributiva, após isso, reduza os termos semelhantes:

Distributiva: a(b+c)=ab+ac.

No item d), temos o produto notável: (a+b)(a-b)=a^2-b^2.

a)

3a(a-b)-2a(a+b)=3a^2-3ab-2a^2-2ab=\boxed{a^2-5ab}

b)

2x(x-3)+x(x-5)=2x^2-6x+x^2-5x=\boxed{3x^2-11x}

c)

(x-3)(x-5)+3x(x+4)=x^2-8x+15+3x^2+12x=\boxed{4x^2+4x+15}

d)

(a+b)(a-b)+(a-2b)(a+5b)=a^2-b^2+a^2+3ab-10b^2=\boxed{2a^2+3ab-11b^2}